Uloga kliničkih puteva u unapređenju kvaliteta liječenja u bolnicama zdravstvene zaštite u bolnicama za pacijente kojima je ugrađen vještački kuk - Štrbac, Savka; Rakić, Severin; Vujić Aleksić, Vesna; Škrbić, Ranko (Scripta Medica, 2020)
Background: Clinical pathways are important tools to achieve better quality of care and to reduce the costs for healthcare system. The total hip replacement (THR) is among the most expensive procedures in health system and the number of these operations has greatly increased in the past decade in the Republic of Srpska. Aim: The aim of the present study was to determine how the implementation of a clinical pathway for THR can influence the length of stay and postoperative complications in hospitals in the Republic of Srpska. Methods: This prospective and comparative study was performed on 2,485 patients who underwent the THR over a 3-year-period in 2012 (prior to the introduction of the clinical pathways, baseline), in 2013 (first evaluation period) and in 2014 (second evaluation period), one and two years after its implementation, respectively. The study was conducted in 10 hospitals in the Republic of Srpska, where the effects of the clinical pathways on length of stay and postoperative complications after THR were measured. Results: The introduction of THR clinical pathways significantly decreased the length of stay in hospital from 14.53 ± 7.03 days measured at baseline, to 12.79 ± 4.81 days and 11.19 ± 4.11 days at first and second evaluation period, respectively. At the same time, the number of early postoperative complications such as death and venous thromboembolism significantly decreased in both groups, while the number of dislocations, as parameter of late complications, decreased just after the second evaluation period. For all other complications, such as revision procedures, infections and periprosthetic fracture, there were no statistical differences after the implementation of clinical pathways. Conclusion: The introduction of clinical pathways was successful in reducing the length of stay in hospitals as well as the postoperative complications after THR.